The Unmet Needs of the Family Caregivers of Patients with Cancer Visiting a Referral Hospital in Iran - Shima Ashrafian; Hossein Feizollahzadeh; Azad Rahmani; Arefeh Davoodi (Elsevier, 2018)
Objective: The complex process of taking care of patients with cancer can affect various aspects of the needs and health of their family caregivers. The present study aims to determine the unmet needs of the family caregivers of patients with cancer and to compare it according to background variables. Methods: The present descriptive study recruited 200 family caregivers of patients with cancer visiting a referral hospital in Iran. Sampling was carried out through the convenience method. Data were collected using Shin's comprehensive needs assessment tool in seven domains (health and psychological problems, family/social support, healthcare staff, information, religious/spiritual support, hospital facilities/services, and practical support). Results: The mean (±standard deviation) of the total scores of the unmet needs of the family caregivers was 81.73 (±16.82), with a possible range of 0-123. A significant percentage of the family caregivers of patients with cancer had unmet needs in all of the seven domains with different severities. The mean scores were higher in the information, healthcare staff (physicians and nurses), and health and psychological problems domains as compared to the other domains. Conclusions: The results showed that the majority of the family caregivers of patients with cancer have many unmet needs, which should be addressed by professional care providers through the development of holistic care programs targeting family caregivers by focusing on information needs and a proper communication process.